The Lithium-ion Battery: Two Breakthroughs in Development and Two Reasons for the Nobel Prize - Yoshino, Akira (Bulletin of the Chemical Society of Japan, 2022)
The author received the 2019 Nobel Prize in Chemistry. Development of the lithium-ion battery, which was the subject of the Prize, is reviewed, highlighting the importance of breakthroughs in basic research and mass production technology research. The importance of these two breakthroughs is emphasized, which is expected to support the success of further R&D essential for the world.